Large sialolith in submandibular gland (Research, Society and Development, 2023)
Introduction: Sialolithiasis is an alteration that affects the salivary glands and is characterized by obstruction of the gland or its excretory duct due to calcified formations called sialoliths. Objective and case report: To report a rare case of large sialolith and conduct a discussion of the diagnosis and treatment of sialolithiasis. A 65-year-old male patient complained of swelling in the left submandibular region, reporting a worsening of the condition after meals, with an evolution of 12 years. In the computed tomography exam, a hyperdense area of 4.0x2.0cm in its largest proportions was observed. The treatment of choice was intraoral removal of the sialolith using a conservative technique with preservation of Warthon's duct through catheterization. Final considerations: Although sialolithiasis is a common oral pathology, the presence of large sialoliths is a rare event that requires knowledge and preparation for proper treatment. The combination of adequate diagnostic methods with thorough and conservative intervention leads to a good prognosis in terms of patient recovery.